The Internet: friend or foe when providing patient education? - Anderson AS; Klemm P (Clinical Journal of Oncology Nursing, 2008)
The Internet has changed how patients with cancer learn about and cope with their disease. Newly diagnosed patients with cancer often have complex educational and informational needs related to diagnosis and treatment. Nurses frequently encounter time and work-related constraints that can interfere with the provision of patient education. They are challenged to educate patients in an environment of rapidly expanding and innovative computer technology. Barriers that hinder nurses in integrating educational Internet resources into patient care include lack of training, time constraints, and inadequate administrative support. Advantages of Internet use for patient education and support include wide-ranging and current information, a variety of teaching formats, patient empowerment, new communication options, and support 24 hours a day, seven days a week. Pitfalls associated with Internet use for patients with cancer include inaccurate information, lack of access, poor quality of online resources, and security and privacy issues. Nurses routinely use computer technology in the workplace and follow rigorous security and privacy standards to protect patient information. Those skills can provide the foundation for the use of online sources for patient teaching. Nurses play an important role in helping patients evaluate the veracity of online information and introducing them to reliable Internet resources.